Negative effects of adverse childhood experiences and absence of positive childhood experiences on healthcare employees: survey findings built on 10 years of trauma-informed development - Williamson, Laneita; Daniel, Stephanie S.; Carter, Jennifer; Ridenhour, Adam; Pulgar, Camila A.; Gay, Yasmin; Debinski, Beata (Frontiers in Public Health, 2025)
IntroductionExisting data on how history of trauma and adversity affects healthcare professionals is limited. This study sought to describe the prevalence of Adverse Childhood Experiences (ACEs) and Positive Childhood Experiences (PCEs) and their association with present-day workplace and wellbeing outcomes among a sample of healthcare teammates overall, as well as specifically among nurses. The paper also describes local trauma-informed care initiatives that supported study feasibility.MethodsCross-sectional online survey data were collected in conjunction with promoting hospital-wide trauma-informed care training opportunities on two campuses that are part of an academic health system. Scales and items assessed independent variables PCEs and ACEs, and dependent variables including burnout, compassion fatigue, organizational belonging, adult resilience, access to support, and workplace violence (WPV). Demographic data were not collected to limit identifiability and encourage participation. Multivariable, hierarchical models regressed categorized total ACEs (ref 0, 1–3, 4–10) and total PCEs (ref 6–7, 3–5, 0–2) together on dichotomized dependent variables. Sub-analyses also adjusted for whether the participant was a nurse or reported serving in a different role.ResultsParticipants included 349 clinical and non-clinical employees, of whom 61.1% had at least one reported ACE, but 24.9% reported 4–10 ACEs. 29.9% reported only having 3–5 PCEs in their childhood, while 23.2% reported 0–2 positive childhood experiences. Even when adjusting for ACEs, having 0–2 PCEs was associated with significantly reduced odds of getting needed emotional or social support (AOR = 0.14, 95% CI: 0.07, 0.29). Having 0–2 PCEs relative to 6–7 PCEs was also significantly associated with greater odds of past 2-week compassion fatigue, a lower resilience score, and decreased odds of reported organizational belonging measures. Adjusting for ACEs and PCEs, nurses reported lower resilience and higher workplace violence compared to all other participant roles combined.DiscussionTeammate history of adversity was widespread and having fewer PCEs was associated with poorer adult workplace outcomes. These findings point to the value of a trauma-informed approach in healthcare, which offers healthcare organizations a framework for recognizing how trauma experiences affect wellbeing and intersect with the healthcare system, as well as how to create environments that are supportive of patients, staff, and providers.